POST CISQ REGIME IN BORDER GOVERNANCE: A Study of the MSME Model in the Aruk Tourism Market - Fadiyah, Dina; Nugroho, Sapto Setyo; Karyana, Ayi; Pasaribu, Daniel; Istianda, Meita; Broto, Mani Festati; Aisyah, Siti (CosmoGov: Jurnal Ilmu Pemerintahan, 2024)
This paper's focus on border governance is motivated by three main points. First, the study of border governance is predominantly dominated by institution-based and policy-based studies. Second, empirically, no research addresses the management of border communities within the Cross Border Post area. Third, theoretically, border governance studies need to revisit the phenomenon of the Custom, Immigration, Quarantine, and Security (CIQS) regime in border governance. This paper raises the question of how the dynamics and survival of border communities reflect border governance, using the MSME model in the Aruk Tourism Market as a case study. This paper argues that border governance in the Aruk region demonstrates practices influenced by the Immigration and Quarantine Security phenomenon following the CIQS regime.gb777